Impact of Intermittent Fasting on Genes Involved in Neurodegenerative Diseases - Siregar, Rizky Amalia; Saraswati, Benedikta Diah (LPPM STIKes Muhammadiyah Ciamis, 2025)
Neurodegenerative diseases, characterized by progressive neuron loss, present a significant global health challenge. Recent research highlights the role of genetic expression in these diseases, with lifestyle interventions, such as dietary changes, shown to influence gene expression linked to neurodegeneration. One promising approach is intermittent fasting (IF), a dietary method alternating fasting and eating periods, which affects biological processes like cellular repair, inflammation, and metabolism. Emerging evidence suggests IF may also alter gene expression related to neurodegenerative diseases, potentially reducing risk and slowing progression. This review examines current studies on the impact of IF on gene expression in neurodegeneration, exploring its mechanisms and implications for new therapeutic and preventive strategies.